Cooperatives and Nigeria's New Tax Regime: Myths and Realities from Academic and Professional Perspectives (Nigerian Journal of Cooperative Economics and Management, 2026)
This research investigates cooperatives and Nigeria's new tax regime myths and realities from academic and professional perspectives. Nigeria's Finance Act 2023 and the Nigeria Tax Administration Act 2025 (NTAA 2025) have introduced sweeping fiscal reforms that carry profound implications for cooperative societies, an institutional pillar of Nigeria's informal and semi-formal economy. Despite cooperatives' constitutional recognition and developmental significance, a persistent myth prevails that these entities enjoy blanket tax exemptions across all income streams. This study interrogates that assumption through the dual lens of academic scholarship and professional practice, exposing the gap between legal myth and legislative reality. Employing a qualitative research design anchored in institutional theory and the benefits-received principle of taxation, the study draws on systematic literature review, documentary analysis of primary tax legislation, and structured key-informant interviews with 24 tax professionals, cooperative administrators, and legal practitioners. Findings reveal that the new regime imposes conditional, activity-based taxation on cooperatives, exempting only surpluses genuinely distributed to members while taxing investment income, commercial activities, and unrelated business income at standard corporate rates. The study provides a myth busting framework, targeted policy recommendations, and a practitioner compliance roadmap, contributing empirical evidence to a field dominated by interpretive confusion and professional misinformation.
Keywords: Cooperatives; Nigeria Tax Administration Act 2025; Finance Act; Tax Exemptions; Cooperative Taxation; FIRS; Compliance